Interactions of host miRNAs in the flavivirus 3´UTR genome: From bioinformatics predictions to practical approaches - Avila-Bonilla, Rodolfo Gamaliel; Salas-Benito, Juan Santiago (Frontiers in Cellular and Infection Microbiology, 2022)
The genus Flavivirus of the Flaviviridae family includes important viruses, such as Dengue, Zika, West Nile, Japanese encephalitis, Murray Valley encephalitis, tick-borne encephalitis, Yellow fever, Saint Louis encephalitis, and Usutu viruses. They are transmitted by mosquitoes or ticks, and they can infect humans, causing fever, encephalitis, or haemorrhagic fever. The treatment resources for these diseases and the number of vaccines available are limited. It has been discovered that eukaryotic cells synthesize small RNA molecules that can bind specifically to sequences present in messenger RNAs to inhibit the translation process, thus regulating gene expression. These small RNAs have been named microRNAs, and they have an important impact on viral infections. In this review, we compiled the available information on miRNAs that can interact with the 3’ untranslated region (3’UTR) of the flavivirus genome, a conserved region that is important for viral replication and translation.